Cassava Peel Starch–Hibiscus rosa-sinensis Leaf Extract: A Plant-Based Alternative Composite for Soft Capsule Shells - Annisa Risdiany; Farikha Maharani; Indah Hartati (Journal of Chemical Process and Material Technology, 2026)
Capsule dosage forms are widely used in pharmaceuticals, with soft capsules offering advantages for liquid and semi-solid formulations. However, conventional gelatin-based shells raise sustainability and halal compliance concerns, prompting the search for plant-based alternatives. This study investigates the development of environmentally friendly soft capsule shells using cassava peel starch, hibiscus leaf gel extract, carrageenan, and glycerin. Hibiscus gel extract was obtained via maceration with 70% ethanol for five days, yielding 40.8%, which meets the Indonesian Herbal Pharmacopoeia standard. Four formulations with varying ratios of starch, gel extract, carrageenan, and glycerin were prepared and tested for disintegration in distilled water and 0.1 N HCl. Results showed that the 1:1:1 formulation with 25% glycerin exhibited the most favorable performance, with disintegration times of 15 minutes in water and 17 minutes, 25 seconds in acidic medium, aligning with pharmacopeial requirements. These findings highlight cassava peel starch and hibiscus gel extract as promising raw materials for sustainable, halal-compliant soft capsule shells, offering an effective alternative to gelatin.